Riffaterre's Semiotic Analysis in Puji Texts - Mulyani, Hesti (Jurnal Penelitian Humaniora, 2025)
The Puji text by KGPAA Mangkunagara IV contains moral teachings that are important to pass on to the younger generation in order to shape noble character and build a strong personality. This study describes the physical form and composition of the text and analyzes its content using Riffaterre's semiotic approach. The method used is descriptive with a Modern Philology approach, with the primary data source being the Puji text. Data collection was carried out through philological research steps such as transcription, translation, and content analysis based on Riffaterre's semiotic method. The analysis includes four main elements: the discontinuity of poetic expression, heuristic and retroactive or hermeneutic readings, matrix, model, and variant, and the hypogram leading to intertextual relations. The results of the study show that the physical form of the text is a printed Javanese script, while its composition is in the form of a single-metric macapat song, Dhandhanggula. Riffaterre's semiotic analysis reveals that the content of the text includes teachings to always pray sincerely for the safety of one's parents, to ask for God's grace or blessings, and that parents who show love and care for others will receive good rewards.